Chinatown kitchen from noodles to nuoc cham ; delicious dishes from Southeast Asian ingredients - Mabbott, Lizzie (London Mitchell Beazley, 2015)
Southeast Asian food is more popular than ever before, but what ARE all those mysterious ingredients in the southeastern section of the supermarket - or, even more so, in your nearest Southeast Asian market? Lizzie Mabbott identifies key ingredients, explains the differences between the 77 types of noodles (not counting "Pot") and tells you how to use them. AND she provides all the recipes you'll need to cook your own delicious meals at home using the tastiest ingredients from China, Malaysia, Vietnam, Thailand, Korea, Japan and all across the region. So tuck in to the authentic (from Grilled Aubergines with Nuoc Cham to Chinese Chive Breads and Korean Summertime Noodles) or the inventive and absolutely delicious (Kimchi Toasted Cheese Sandwich, Tempura Soft-Shell Crab Burgers and Chinese Spag Bol), and cook your way around the Asian supermarket.--Provided by publisher.
Keywords: Cooking, Southeast Asian; Cooking, Chinese; Southeast Asia -- Social life and customs